Taxation and female labor supply in Italy - Fabrizio Colonna; Stefania Marcassa (IZA Journal of Labor Policy, 2015)
Italy has the lowest labor supply of married women among EU countries. Moreover, the participation rate of married women is positively correlated with their husbands' income. We show that these two features can be partly explained by the tax system: a high tax rate together with tax credits and transfers raise the burden of two-earner households, generating disincentives to work. We estimate two structural models of labor supply: one where the husband's labor supply is inelastic and one with joint couple decisions. Then we use the estimated parameters to simulate the effects of alternative revenue-neutral tax systems on labor supply. We find that working tax credit and gender-based taxation boost it, with the effects of the former being concentrated on low educated women. Conversely, joint taxation implies a drop in the participation rate.
Keywords: J21; J22; H31; 330; Female labor force participation; Italian tax system; Second earner tax rate; Joint taxation; Gender-based taxation; Working tax credit